The Present Situation of Academic Guidance for New Students in the Palestinian Universities: A Case Study of the Islamic University - Gaza - Fayez Kamal Sheldan; Samia Samir Arheem (University of Science and Technology, Yemen, 2019)
The study aimed at assessing the present situation of academic guidance for new students in the Palestinian universities and the ways to improve it. The researchers conducted this study in the Islamic University as a case study. Thus, the researchers followed the analytical descriptive method and used a questionnaire and an interview as tools for data collection. The study sample consisted of (285) students. The main results of the study were as follows: The present situation of the academic guidance for new students in the Islamic University had a high degree with a relative weight (%75.80), and there were no statistically significant differences between the means of the sample ratings on the present situation of the academic guidance for new students in the Islamic University due to gender variable except the dimension of social guidance which was in favor of female students. However, there were statistically significant differences due to major variable for the students of humanities, as well as due to a cumulative mean variable for students who have (85% and more) except for the dimensions of study guidance and vocational guidance. Finally, the researchers presented suggestions to improve the present situation of the academic guidance for new students in the Islamic University. Keywords: academic guidance, the new students, the Islamic University, the Palestinian universities